Temperature, salinity and pH dependence of zinc oxide photocatalytic properties for dye removal application / Wan Rafizah Wan Abdullah... [et al.] - Wan Abdullah, Wan Rafizah; Mohd Nazri, Nur Mimi Nazira; Ismail, Nur Ain; Dzulkarnain, Farahana Atikah; Mohd Ghazali, Mohd Sabri (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
ZnO based photocatalysis process is considered as promising cost-effective and environmental friendly technology to decompose recalcitrant organic contaminants in water by converting them into CO2 and H2O. Existing photocatalysis of ZnO commonly involve the near-room-temperature photoreaction under illumination of the UV light or sunlight. In this study, the influence of operational conditions such as temperature, salinity and pH on photocatalytic activity of Zn were thoroughly investigated. Methylene blue (C16H18N3SCl), (MB) dye was selected as the model contaminant. 10 mg/L of MB dye was photodegraded under UV-light irradiation in the present of 1 g/L of ZnO for 60 minutes. The reaction was conducted under different sets of operational conditions such as temperature (30 – 45 oC), salinity (25-100 g/L NaCl) and pH (5-9). The optimum operational condition for the photodecomposition of MB using ZnO catalyst were found to be at high temperature (45 oC), low pH (pH 5) and high salinity (100 g/L NaCl)